Vanadium Mineralization in the Kola Region, Fennoscandian Shield - Alena A. Kompanchenko; Anatoly V. Voloshin; Victor V. Balagansky (Minerals, 2018)
In the northern Fennoscandian Shield, vanadium mineralization occurs in the Paleoproterozoic Pechenga⁻Imandra-Varzuga (PIV) riftogenic structure. It is localized in sulfide ores hosted by sheared basic and ultrabasic metavolcanics in the Pyrrhotite Ravine and Bragino areas and was formed at the latest stages of the Lapland⁻Kola orogeny 1.90⁻1.86 Ga ago. An additional formation of vanadium minerals was derived from contact metamorphism and metasomatism produced by the Devonian Khibiny alkaline massif in the Pyrrhotite Ravine area. Vanadium forms its own rare minerals (karelianite, coulsonite, kyzylkumite, goldmanite, mukhinite, etc.), as well as occurring as an isomorphic admixture in rutile, ilmenite, crichtonite group, micas, chlorites, and other minerals. Vanadium is inferred to have originated from two sources: (1) basic and ultrabasic volcanics initially enriched in vanadium; and (2) metasomatizing fluids that circulated along shear zones. The crystallization of vanadium and vanadium-bearing minerals was accompanied by chromium and scandium mineralization. Vanadium mineralization in Paleoproterozoic formations throughout the world is briefly considered. The simultaneous development of vanadium, chromium and scandium mineralizations is a unique feature of the Kola sulfide ores. In other regions, sulfide ores contain only two of these three mineralizations produced by one ore-forming process.